RECOVERY AND REUSE OF WASTE TETRA PAK PACKAGES BY USING A NOVEL TREATMENT - Martinez-Barrera, Gonzalo; De la Colina-Martinez, Ana L.; Martinez-Lopez, Miguel; Jose del Coz-Diaz, Juan; Gençel, Osman; Avila-Cordoba, Liliana; Barrera-Diaz, Carlos E.; Gençel, Osman (Woodhead Publ Ltd, 2019)
[Abstract not Available]
Keywords: Gamma-Radiation; Cellulose; Aluminum; Behavior